2000
DOI: 10.1054/bjoc.1999.1049
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Hodgkin’s disease by Epstein-Barr virus (EBV) status: prior infection by EBV and other agents

Abstract: A UK population-based case–control study of Hodgkin's disease (HD) in young adults (16–24 years) included 118 cases and 237 controls matched on year of birth, gender and county of residence. The majority (103) of the cases were classified by Epstein–Barr virus (EBV) status (EBV present in Reed–Stenberg cells), with 19 being EBV-positive. Analyses using conditional logistic regression are presented of subject reports of prior infectious disease (infectious mononucleosis (IM), chicken pox, measles, mumps, pertus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
86
2
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 13 publications
5
86
2
8
Order By: Relevance
“…Sleckman et al 11 found no association with education, income, childhood housing, sibship size or birth order when comparing 16 EBV-positive to 67 EBV-negative U.S. patients aged 15-55 with early-stage HL. Findings from the latter 2 studies do not support a delayed-exposure mechanism but also may not be directly comparable to ours as both used hospital-based patients, one was limited to early-stage disease 11 and neither stratified findings in women by age; 11,12 our differences with the findings of Alexander et al 13 for EBV-negative HL may be due in part to the much narrower age range of their subjects. Contradicting the delayed-exposure hypothesis in our data for young adults are the risk of EBV-positive HL with lower birth order and the lack of association with self-reported IM, a clinically evident expression of infection delayed past childhood.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Sleckman et al 11 found no association with education, income, childhood housing, sibship size or birth order when comparing 16 EBV-positive to 67 EBV-negative U.S. patients aged 15-55 with early-stage HL. Findings from the latter 2 studies do not support a delayed-exposure mechanism but also may not be directly comparable to ours as both used hospital-based patients, one was limited to early-stage disease 11 and neither stratified findings in women by age; 11,12 our differences with the findings of Alexander et al 13 for EBV-negative HL may be due in part to the much narrower age range of their subjects. Contradicting the delayed-exposure hypothesis in our data for young adults are the risk of EBV-positive HL with lower birth order and the lack of association with self-reported IM, a clinically evident expression of infection delayed past childhood.…”
Section: Discussioncontrasting
confidence: 80%
“…The inconsistencies of our findings with the delayed-exposure etiologic model for HL and with other published findings [11][12][13][14][15] have several possible explanations. (i) The proportion of HL tumors that are EBV-positive has been shown to vary markedly with the composition of the patient population.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations